Early ecological shifts of soil fungal communities after a historic megafire in the Sierra de la Culebra - Jorge Víctor Maurice-Lira; Claudia Prada-Polo; Dante Bertocci; Ignacio Sanz-Benito; Pablo Martín-Pinto (Trees, Forests and People, 2025)
Megafires represent an escalating global challenge, with Mediterranean regions particularly vulnerable due to intensifying droughts and rising temperatures. Studying the impacts of megafire on biodiversity and ecosystem services is crucial for strengthening resilience against this phenomenon. In this study, we evaluated the short-term impact of Spain’s largest recorded megafire on soil fungal diversity. We hypothesized: (i) fungal richness and abundance would be lower in burned plots than in control plots; (ii) saprotrophic species and ectomycorrhizal fungi (ECM) would exhibit divergent abundance trends; and (iii) indicator taxa associated with post-fire environments would be significantly linked to burned plots. To assess the validity of these hypotheses, next-generation sequencing techniques were applied. A total of 3025 operational taxonomic units were identified, of which 2188 were assigned at the genus or species level, spanning 18 phyla. Ascomycota and Basidiomycota were the dominant phyla. Taxa were grouped into 20 trophic guilds, with saprotrophic fungi (67 %) and ECM fungi (18 %) dominating. Diversity indices considering relative abundances (Shannon and Pielou Evenness) were significantly lower in burned plots. Multivariate analyses revealed differences in fungal composition and functional groups. ECM taxa were significantly associated with unburned soils, whereas several saprotrophic groups were associated with burned plots, demonstrating divergent trends between these guilds in post-fire environments. Moreover, some pyrophilic taxa were identified as indicators of burned plots. Edible taxa were significantly affected, potentially threatening rural economies. Our findings provide robust insights into how megafires threaten both fungal diversity and its ecosystem services and emphasize the need for effective fire-prevention strategies.